Fiscal consolidations in the Central and Eastern European countries - António Afonso; Christiane Nickel; Philipp Rother (European Central Bank (ECB), 2005)
We study fiscal consolidations in the Central and Eastern European countries and what determines the probability of their success. We define consolidation events as substantive improvements in fiscal balances adjusting for the impact of cyclical effects. We use Logit models for the period 1991–2003 to assess the determinants of the success of a fiscal adjustment. The results seem to suggest that for these countries expenditure based consolidations have tended to be more successful. By contrast, revenue based consolidations have a tendency to be less successful.
Keywords: C25; E62; H62; 330; central and eastern Europe; fiscal episodes; Fiscal Policy; Logit models; Konzernabschluss; Haushaltsdefizit; Öffentliche Finanzen; Osteuropa